MicroRNA-494 inhibits breast cancer progression by directly targeting PAK1 - Zhan, Meng-Na (Cell Death Dis, 2017)
MicroRNA (miRNA) is involved in the progression and metastasis of diverse human cancers, including breast cancer, as strong evidence has been found that miRNAs can act as oncogenes or tumor suppressor genes. Here, we show that miR-494 is decreased in human breast cancer specimens and breast cancer cell lines. Ectopic expression of miR-494 in basal-like breast cancer cell lines MDA-MB-231-LUC-D2H3LN and BT-549 inhibits clonogenic ability and metastasis-relevant traits in vitro. Moreover, ectopic expression of miR-494 suppresses neoplasm initiation as well as pulmonary metastasis in vivo. Further studies have identified PAK1, as a direct target gene of miR-494, contributes to the functions of miR-494. Remarkably, the expression of PAK1 is inversely correlated with the level of miR-494 in human breast cancer samples. Furthermore, re-expression of PAK1 partially reverses miR-494-mediated proliferative and clonogenic inhibition as well as migration and invasion suppression in breast cancer cells. Taken together, these findings highlight an important role for miR-494 in the regulation of progression and metastatic potential of breast cancer and suggest a potential application of miR-494 in breast cancer treatment.